2004
DOI: 10.3844/ajassp.2004.215.219
|View full text |Cite
|
Sign up to set email alerts
|

Development of Growth Medium for Centella Asiatica Cell Culture Via Response Surface Methodology

Abstract: Abstract:The effects of sucrose, Indole-3-Acetic Acid (IAA) and 6-BenzylAminoPurine (BAP) concentrations on cell growth of Centella asiatica cell suspension culture were studied. The concentrations were designed using Central-composite experimental design and regression analysis was carried out to obtain response surface model describing cell growth for prediction of optimum conditions. Only sucrose as a single factor was positively significant for cell growth. Increasing sucrose concentration from 3.32 to 6.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In C. asiatica cell suspension cultures, RSM applied for the optimization of sucrose, IAA, and 6benzylaminopurine (BAP) and results revealed sucrose as a prime factor for cell growth. 30 Several studies found the significance of applying RSM. 22 RSM was used for the optimization of basal media components (sucrose, nitrogen, and phosphorus) for maximum production of β-carotene from D. carota cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. asiatica cell suspension cultures, RSM applied for the optimization of sucrose, IAA, and 6benzylaminopurine (BAP) and results revealed sucrose as a prime factor for cell growth. 30 Several studies found the significance of applying RSM. 22 RSM was used for the optimization of basal media components (sucrose, nitrogen, and phosphorus) for maximum production of β-carotene from D. carota cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…max suspension cultures was achieved. In the same way, this RSM technique has been applied successfully nowadays in many biotechnological and biochemical studies, such as in vitro growth characteristics of Centella asiatica, β-carotene in D. carota, lycopene from suspension cultures of L.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by George et al (2000) indicated that higher sucrose concentration with low NAA and higher BAP resulted in maximum shoot length. Similar studies have also been done where RSM-CCD was used for the development of cell culture medium of Centella asiatica where the effects of sucrose, IAA and BAP were studied where maximum dry cell weight was obtained at 6% sucrose and 1 mg.L -1 of BAP and IAA (Omar et al, 2004). Naveenchandra et al (2011) also observed that maximum sucrose concentration was one of the contributing factors for high shoot initiation.…”
Section: Regression and Statistical Analysismentioning
confidence: 94%
“…This method has been applied to optimize biochemical and physical process in many researches (Cansee et al, 2008;Omar et al, 2004;Zhu et al, 2010;Xu et al, 2008;Narkprasom et al, 2013) because, this excellent design spends minimal experiment to obtain the best outcome.…”
Section: Introductionmentioning
confidence: 99%